Justice for Child Offenders: A Humanistic Legal Approach - Sekaring Dyah Ika Wulan; Riki Apriyansyah; Mochamad Ali Rizza; Abdel Salam Atwa Ali Al Fandi (Journal of Human Rights, Culture and Legal System, 2025)
This study examines the implementation of the juvenile criminal justice system, which prioritizes Restorative Justice and applies Diversion to resolve cases involving juvenile offenders. This approach emphasizes restoring social cohesion and relationships rather than imposing financial compensation. However, the lack of clear provisions within the legal framework has resulted in Restorative Justice being neither distinctly nor effectively regulated, despite its critical importance. This study aims to evaluate juvenile justice implementation, identify legal gaps, and propose regulatory reconstruction to enhance Restorative Justice effectiveness. This research employs a constructivist paradigm with a socio-legal approach, using descriptive methods and secondary data, including primary, secondary, and tertiary legal sources. Data collection was conducted through literature review and qualitative analysis. The findings indicate that legal protection for children as perpetrators remains insufficient, as current regulations focus on the child’s actions rather than the child as a subject of protection. Key weaknesses are identified in three aspects: legal substance, legal structure, and legal culture. There are no specific provisions for Restorative Justice, law enforcement agencies lack coordination, and public understanding of Restorative Justice remains limited. The study recommends reconstructing regulations to align legal protection with the principles of justice, ensuring that the rights, rehabilitation, and reintegration of child offenders are fully protected.